Gender Stereotypes in Some Romantic Travelogues (and How to Use Them) - Anne ROUHETTE (E-REA)
This article looks at Romantic travel literature from a gendered perspective. After general considerations on the masculine dimension of travel writing, I focus on three narratives presented as having been written by a woman, more or less in collaboration with her husband. My purpose here is not to look for a specifically masculine or feminine type of travel writing, but to analyse how the openly gendered dimension of the text impacts its reception, to the extent that it may be said to partake of a strategy aiming at conveying a sometimes radical discourse.